1986
DOI: 10.2320/matertrans1960.27.656
|View full text |Cite
|
Sign up to set email alerts
|

Solid Solution Hardening of Nickel —Role of Transition Metal and B-subgroup Solutes—

Abstract: A systematic investigation is made on the solid solution hardening of binary nickel alloys with additions of B-subgroup and transition metal elements. The 0.2% flow stress at 77 K and the Young's modulus are measured for a variety of binary alloys to evaluate the rate of solution hardening per one available data on the rate of change in lattice constant (da/dc), interpretation of the solution hardening that the hardening is more intense by the additions of transition metal elements than by the additions of B-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
61
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 175 publications
(72 citation statements)
references
References 33 publications
(8 reference statements)
8
61
0
3
Order By: Relevance
“…pct 2/3 (see Figure S2 in Supplementary Material)-taking into account of the large scatter in the data, this value compares well with that obtained in the present study. In addition, these results are qualitatively consistent with the compressive flow stress data of Mishima et al [31] In Reference 31 the flow stress of~100 MPa of pure Ni was retained on addition of~2 at. pct Fe and increased to~150 MPa for an 8 at.…”
Section: Ni-based Binary Alloyssupporting
confidence: 82%
See 3 more Smart Citations
“…pct 2/3 (see Figure S2 in Supplementary Material)-taking into account of the large scatter in the data, this value compares well with that obtained in the present study. In addition, these results are qualitatively consistent with the compressive flow stress data of Mishima et al [31] In Reference 31 the flow stress of~100 MPa of pure Ni was retained on addition of~2 at. pct Fe and increased to~150 MPa for an 8 at.…”
Section: Ni-based Binary Alloyssupporting
confidence: 82%
“…These are in qualitative agreement with the experimental results. The observed SSH is also in good agreement with the literature [9,[31][32][33] on macroscopic mechanical testing. The k values of 411 and 11 MPa/at.…”
Section: Ni-based Binary Alloyssupporting
confidence: 80%
See 2 more Smart Citations
“…Suzuki's group studied solid solution hardening in Ni-X binary alloys and Ni-40 at%Co-X ternary alloys, reporting that solid solution hardening in alloys with the solubility limit became larger than that of alloys with a completely miscible similarly to the present result. [17][18][19] It was also reported that an extra hardening observed in the former type of alloys increased with a reduction of the solubility limit. Thus, in the present Pt-based binary alloys, the relationship between the increment in hardness and an inverse of the solubility limit in a respective alloy was investigated, of which result is in Fig. 14.…”
Section: Solid Solution Hardening Due To Various Solutementioning
confidence: 98%